2017
DOI: 10.1186/s12889-016-3987-8
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of outdoor school environments to promote physical activity in Delhi, India

Abstract: BackgroundIncreasing physical activity in children is an important public health goal in India. Schools may be a target for physical activity promotion, but little is known about outdoor school environments. The purpose of this study was to describe characteristics of the surrounding outdoor school environments that may promote children’s physical activity in Delhi, India.MethodsFor this cross-sectional study, we conducted a structured observation of outdoor school environments in a random sample of 16 private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…In addition, ndings from this study revealed the dearth of equipment and sporting facilities in the schools. These ndings are similar to those obtained from studies in other countries [41,44,45]. This situation has compromised physical health education classes in schools in Nigeria resulting in an emphasize on the delivery of theoretical concepts to the in-school adolescents to the detriment of eld based activities.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, ndings from this study revealed the dearth of equipment and sporting facilities in the schools. These ndings are similar to those obtained from studies in other countries [41,44,45]. This situation has compromised physical health education classes in schools in Nigeria resulting in an emphasize on the delivery of theoretical concepts to the in-school adolescents to the detriment of eld based activities.…”
Section: Discussionsupporting
confidence: 86%
“…For example, the aesthetic satisfaction of students who find the recess period to be sufficient is higher compared to those who do not find recess period sufficient. Tarun et al, in their study on 16 private schools, emphasized that the aesthetic qualities of the locations in which out-of-school free activities are conducted, are very important [78]. In their studies investigating the problems students face in their free time, Cengiz and Dogtaş stated that difficulties were predominantly experienced in relation to security, aesthetics, and in the use of open, green spaces [79].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Tarun et al investigated 16 schools in Delhi, India, based on a field audit tool combined with structured outdoor observation [11]. They utilized the SPEEDY (Sport, Physical activity and Eating behavior: Environmental Determinants in Young people) audit tool developed by Van Sluijs et al [12] and validated in the U.K. [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Initially, a checklist with a yes or no response format was prepared for pilot assessment of schools based on the factors related to the safety and operation of school sites commonly mentioned in the literature [9][10][11]. From the items listed under "neighborhood-level walkability" in the study by Zhu and Lee, sidewalk completeness for the use of pedestrians, street connectivity, and land-use (residential, commercial, or mix) were considered excluding dynamic items such as estimations of potential walkers and neighborhood density [10].…”
Section: Initial School Audit Tool Developmentmentioning
confidence: 99%